Dietary mycotoxins: an overview on toxicokinetics, toxicodynamics, toxicity, epidemiology, detection, and their mitigation with special emphasis on aflatoxicosis in humans and animals - Kibugu, J.; Munga, L.; Mburu, D.; Maloba, F.; Auma, J.E.; Grace, Delia; Lindahl, Johanna F. (MDPI, 2024)
Mycotoxins are secondary metabolites of filamentous fungi and ubiquitous dietary contaminants. Aflatoxins, a group of mycotoxins with high prevalence and toxicity, have raised a high level of public health concern, the most prevalent and toxic being aflatoxin B1 (AFB1). Many aspects appertaining to AFB1 poisoning are not well understood. Yet this information is necessary to devise appropriate surveillance and mitigation strategies against human and animal aflatoxicosis. This review provides an in-depth update of work carried out on mycotoxin poisoning, particularly aflatoxicosis in humans and animals, to identify gaps in knowledge. Hypotheses explaining the functional significance of mycotoxins in fungal biology and their dietary epidemiological data are presented and briefly discussed. The toxicology of aflatoxins and the challenges of their mitigation are discussed in depth. It was concluded that the identification of potential mycotoxin-hazard-prone food items and quantification of the associated risk of cancer ailments in humans is a prime priority. There is a dearth of reliable sampling methodologies for estimating AFB1 in animal feed. Data update on AFB1 in animal feed and its implication in animal production, mitigation strategies, and elucidation of risk factors to this hazard is required. To reduce the burden of aflatoxins, surveillance employing predictive technology, and biocontrol strategies seem promising approaches.